APPLICATION OF READING LITERACY ON SPEAKING SKILLS IN SPEAKING TEXT - Nur Indarwati; Muhammad Zakia Firdaus; Tsalitsatul Maulidah (Prodi Tadris Bahasa Inggris, 2022)
This study aims to determine the effect of reading text or speech literacy on speaking skills in speech and the results of students' speaking skills in speech text material in Indonesian subjects. This research is a quantitative research, this research is focused on reading literacy which is related to the speaking skills of students in speech text material, along with the factors that influence these two things. The research data was taken in June 2021. The research data was obtained using two techniques in two classes, the experimental class using the practical method and for the control class using the lecture method. The research data was then calculated using SPSS 16 to determine whether the data taken in the experimental and control classes had an effect on students or not. The results of the first study were using pre-test data and for the second research results, namely post-test data. From these data, researchers can conclude the results that have been obtained in carrying out the practice of giving speeches in class..